A comparison of medication adherence/persistence for asthma and chronic obstructive pulmonary disease in the United Kingdom. Issue 10 (5th May 2014) - Covvey, J. R.; Mullen, A. B.; Ryan, M.; Steinke, D. T.; Johnston, B. F.; Wood, F. T.; Boyter, A. C.
Summary Aim To describe and compare adherence and persistence with maintenance therapies in patients with asthma or chronic obstructive pulmonary disease (COPD) in the United Kingdom (UK). Methods A retrospective prescribing database cohort was obtained from 44 general practitioner surgeries in National Health Service Forth Valley Scotland. Patients with physician‐diagnosed asthma or COPD who received maintenance therapy between January 2008 and December 2009 were included. Five classes of therapy were assessed: inhaled corticosteroids, long‐acting beta‐agonists, combination therapy inhalers, theophyllines and long‐acting muscarinic antagonists. Adherence was calculated using the medication possession ratio (MPR) and persistence was determined using Kaplan–Meier survival analysis for the time to discontinuation (TTD) over 1 year. Two step‐wise logistic regressions were performed to assess the contribution of diagnosis to adherence/persistence. Results A total of 13, 322 patients were included in the analysis: 10, 521 patients with asthma and 2801 patients with COPD. 25.2% of medication episodes for asthma and 45.6% of medication episodes for COPD were classified as having an adequate medication supply (MPR of 80–120%). The overall median TTD was 92 days (IQR, interquartile range: 50–186 days) for patients with asthma and 116 days (IQR: 58–259 days, comparison p < 0.001) for patients with COPD. Patients with COPD were found to be more likely to achieve an MPR of at least 80% (OR: 1.27, 95% CI: 1.15–1.40), but had a similar likelihood of persistence at 1 year to patients with asthma. Conclusion Adherence and persistence with respiratory therapies in the UK is relatively low. There is suggestion that patients with COPD may display more adherent behaviours than patients with asthma.